Tipos de fisuras labiopalatinas presentes en los neonatos del Hospital Isidro Ayora de la ciudad de Loja con labio fisurado y palar hendido según la clasificación de la Universidad de IOWA de los Estados Unidos en el periodo de atención 2010-2014 - Costa Mora, Salomé del Cisne (2015)
Congenital anomalies have a high frequency in our social environment but one of the most common is cleft lip and palate. This anomaly can be present at any social class, economic and educational level and in any racial group. Clefts are thought to be of multifactorial etiology, the most important factors include: congenital, hereditary and environmental. The purpose of this study was to make a frequency of the most cleft lip and palate based on the classification of Iowa university in newborn of Loja, with a diagnose of left cleft lip and palate. The poblation was of 2080 newborns attended in this period, and the sample was 29 newborns. The results says that the most frequency was the masculine gender with a 63%, the fissure most frequent was the right alveoli palate complete with a 42%, and the year who give more newborns with cleft palate was in 2011. With this information we can show who is de most of the problems in our city an help to the doctors and they could be prepare for made the right treatment.